PENYEDIAAN DESAIN SEKAT BELAJAR DI SMK TRIGUNA JAKARTA SELATAN UNTUK PROGRAM LURING NEW NORMA - Nina Carina; Mekar Sari Suteja; Maria Veronica Gandha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
The practice of New Normal during the COVID-19 pandemic has affected the education system. The implementation of WFH (work from home) or BDR (learning from home) becomes a mandatory requirement all red zone areas in Indonesia. Some drawbacks from BDR are occurred, including the lack of accuracy in teaching material delivery and the lack of supporting facilities for learning from home also found in the teaching activities in SMK Triguna 1956. As the Jakarta Pintar cardholders, the students in this school were not able to carry out online exams due to the absence of such facilities in their homes. Based on that, the school management had submitted a proposal for practical exams in the school, especially for class XII students. This proposal led to the procurement of a supporting facility for COVID-19 transmission prevention, such as the use of a partition that should not obstruct student’s view of the blackboard which is expected to minimize the risk of transmission through droplets and airborne. In collaboration with the UNTAR’s PKM Team, several research activities were undertaken, including literature studies, discussions with teachers and school principals, spatial surveys, material assessment, as well as space measurements. The results from this research propose three design alternatives and five kinds of partition. The entire partitions were built as a mock up and been tested for their rigidity, visual ease, and the movement space. From those tests, the most recommended design was selected and followed by mass duplication per necessary needs. Through the partition installations in the classroom of SMK Triguna 1956, it is hoped to encourage the class XII students in the face-to-face teaching (offline learning), and it can also facilitate the examination properly to meet the prevention rules of COVID-19 transmissionABSTRAK:Pemberlakukan New Normal selama pandemi COVID-19 mempengaruhi sistem pendidikan. Penerapan sistem WFH (work from home) atau BDR (belajar dari rumah) menjadi hal wajib di seluruh daerah dengan kategori zona merah di Indonesia. Beberapa kekurangan BDR seperti tidak tersampaikannya materi ajar secara akurat dan kurangnya fasilitas pendukung belajar dirumah yang memadai menjadi masalah utama yang dijumpai pada kegiatan belajar di SMK Triguna 1956. Sebagai pemegang Kartu Jakarta Pintar, murid-murid di sekolah ini tidak dapat melaksanakan ujian daring (dalam jaringan) karena ketiadaan fasilitas di rumah para siswanya. Berdasarkan hal tersebut, pengelola sekolah mengajukan usulan ujian praktik di sekolah, khususnya bagi siswa kelas XII. Hal ini memerlukan pengadaan fasilitas pendukung protokol pencegahan penularan COVID-19, seperti penggunaan partisi yang diharapkan dapat memperkecil resiko penularan melalui droplet maupun airborne tanpa menghalangi pandangan siswa ke papan tulis. Bekerja sama dengan Tim PKM UNTAR, beberapa kajian dilakukan seperti studi literatur, diskusi dengan guru dan kepala sekolah, survei ruang, studi bahan hingga pengukuran ruang gerak. Kemudian dihasilkanlah 3 alternatif desain dan 5 macam contoh partisi. Keseluruhan contoh partisi dibuat mock up nya dan diuji terhadap kekakuan dan kekuatan bahan, kebebasan visual dan ruang gerak. Dari hasil tersebut diperoleh 1 desain yang paling direkomendasikan untuk menjadi sekat belajar dan digandakan sesuai jumlah kebutuhan. Dengan terpasangnya partisi pada ruang kelas SMK Triguna 1956 dari kegiatan PKM, diharapkan dapat mendukung siswa kelas XII untuk pelaksanaan pembelajaran tatap muka dengan sistem luring (offline), serta memberikan fasilitas memadai bagi pelaksanaan ujian yang memenuhi protokol kesehatan guna pencegahan penyebaran COVID-19